2020
DOI: 10.1002/jocb.466
|View full text |Cite
|
Sign up to set email alerts
|

The Vital Few: Exploring the Role of Expertise in the Process of Team Creativity

Abstract: This study provides insight into the role of expertise in the process of team creativity. Existing process models, that is, the random variation model and the creative synthesis model, either fail to treat team as an independent creative entity or neglect the differentiation in the voice of individual members in team creative process. In contrast, this study recognizes the role of expertise in shaping the process of team creativity and presents an alternative model, the vital few model (experts as “vital few”)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Even someone who is a highly original thinker will probably fail without communicating effectively with other team-members or when being unable to accept constructive critique. At the same though, individual-level factors explain a far more substantial portion of companies' effectiveness that it is usually assumed (Mollick, 2012), and a vital few experts within the team can create a difference that leads to creative successes (Zhang et al, 2020).…”
Section: Workmentioning
confidence: 99%
“…Even someone who is a highly original thinker will probably fail without communicating effectively with other team-members or when being unable to accept constructive critique. At the same though, individual-level factors explain a far more substantial portion of companies' effectiveness that it is usually assumed (Mollick, 2012), and a vital few experts within the team can create a difference that leads to creative successes (Zhang et al, 2020).…”
Section: Workmentioning
confidence: 99%
“…In the same vein, Tan et al (2019) stated that research and practice in musical creativity require shared efforts between students and educators. Furthermore, researchers have suggested that musical creativity is even more likely to emerge when students collaborate with various experts (Zhang, Li, & Yan, 2020).…”
Section: Pedagogical Keys To Foster Musical Creativitymentioning
confidence: 99%